The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/brs.0000000000004140
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mid-Term Outcomes Between ACDF and Minimally Invasive Posterior Cervical Foraminotomy in the Treatment of Cervical Radiculopathy

Abstract: Study Design. Retrospective cohort study. Objective. To compare minimally invasive posterior cervical foraminotomy (MI-PCF) and anterior cervical discectomy and fusion (ACDF) in the treatment of unilateral cervical radiculopathy. Summary of Background Data. MI-PCF has been shown to be equally effective as ACDF in treating cervical radiculopathy due to foraminal stenosis and similar pathologies. Additionally, it has been hypothesized that preserving motion and avoiding fusion reduces risk for adjacent segment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Building on prior retrospective cohort studies, 8,9 Ruetten et al performed a prospective, randomized controlled study comparing 100 ACDF to 100 PCF patients with lateral cervical disk herniation and found no significant differences between cohorts in perioperative complications or two-year revision rates 10 . Another randomized control trial by Wirth et al found no significant difference in combined scores of pain improvement, resolution of neurological defects, return to work at two-month follow-up, or rates of reoperation 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on prior retrospective cohort studies, 8,9 Ruetten et al performed a prospective, randomized controlled study comparing 100 ACDF to 100 PCF patients with lateral cervical disk herniation and found no significant differences between cohorts in perioperative complications or two-year revision rates 10 . Another randomized control trial by Wirth et al found no significant difference in combined scores of pain improvement, resolution of neurological defects, return to work at two-month follow-up, or rates of reoperation 11 …”
Section: Discussionmentioning
confidence: 99%
“…The literature comparing outcomes for single-level ACDF versus PCF is mixed. In terms of retrospective cohort studies, Lin et al showed PCF is associated with higher rates of reoperation compared with ACDF, 8 while Emami et al found no difference in reoperation rates 9 . Building on these, randomized control studies by Ruetten et al 10 and Wirth et al 11 found no significant differences in postoperative complication or reoperation rates.…”
mentioning
confidence: 99%
“…This reoperation rate is comparable with the reoperation rates of ACDF, ie 7.8% to 15%. 29 , 30 Kessinger studied the rate of reoperation after PCN and identified a reoperation rate of 19.5% in his study population of 133 patients. 31 This rate appears to be somewhat higher than the rate we found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of technology in recent years, for some cervical spondylotic radiculopathy, the posterior endoscopic cervical foraminoplasty can also alleviate pain very well without increasing the repair rate and complications [20]. Cervical disc replacement can preserve the motor function of surgical segments and theoretically reduce the probability of degeneration of adjacent segments.…”
Section: Discussionmentioning
confidence: 99%